RARE-16. CLINICAL AND HISTOPATHOLOGICAL CHARACTERISTICS OF YOUNG ADULTS WITH GLIOBLASTOMA AT DIAGNOSIS. (5th November 2018) - Vaslow, Zachary; Kirkpatrick, John; Affronti, Mary; Healy, Patrick; Herndon, James; Lipp, Eric; Thomas, Leslie; Johnson, Margaret; Randazzo, Dina; Desjardins, Annick; Friedman, Henry; Ashley, David; et al.
Abstract: BACKGROUND: Glioblastoma (GBM) occurs commonly in 6th to 7th decades of life. GBM in young adults (age 18–39 yrs) is rare and the implications of this diagnosis during young adulthood has different considerations than in their older counterparts. We planned to identify young adults with GBM and to evaluate the clinical and histopathological factors in this rare group. METHODS: We queried retrospectively an IRB-approved database registry from 12/2004- 10/2016. We included GBM patients by these factors: 1. Age at diagnosis as 18–39 yrs, 2. Confirmed GBM pathology at initial diagnosis, and 3. Usable information on time to first progression. We excluded patients with an initial diagnosis of WHO grades II-III glioma. We obtained available clinical and histopathological information. We estimated progression-free survival (PFS) and overall survival (OS) using Kaplan-Meier methods. RESULTS: We found 184 young adult patients that met our criteria for inclusion in this evaluation. Median age was 33 yrs with a majority being males (n=109, 59.2%). The majority (89.1%) had surgical resection at time of diagnosis (GTR, n=106 and STR, n=58). Median OS was 41.6 mos (95% CI: 31.2, 51.6), with a 5-year OS of 38.9% (95% CI: 31.2%, 46.5%). Median PFS was 17.2 mos (95% CI: 14.1, 21). Recurrence occurred in 148 patients (80%) and 25% (n=37) were enrolled in clinical trials after 1st recurrence. While most had pathology described as GBM, there were 50 variants (27.2%) including giant cell (n=20), small cell (n=15), oligodendroglial (n=10), PNET (n=4), and rhabdoid (n=1). Known IDH1 status was 29 mutant (15.8%) and 51 wild type (27.7%) CONCLUSIONS: Diagnosis of GBM in young adults associated with a longer OS. Surgical resection at diagnosis and participation in clinical trials are common. Histopathology for this group can be heterogeneous. Providers should tailor treatment and survivorship planning uniquely to the young adult GBM population.